2000
DOI: 10.1063/1.125863
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the energy levels of self-assembled InAs quantum dots by rapid thermal annealing

Abstract: We studied the photoluminescence spectra of rapid-thermal-annealed self-assembled InAs quantum dots at 10 K. For annealing temperatures ranging from 700 to 950 °C, we observed a blueshift in the interband transition energies, a decrease in the intersublevel spacing energies, and a narrowing of photoluminescence linewidths. In this letter, we demonstrate that the tuning of the InAs quantum dots interband transition and intersublevel spacing energies can be achieved by 30 s of rapid thermal annealing. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 13 publications
2
39
0
Order By: Relevance
“…This is due to a fast Ga outdiffusion has been shown that the three-dimensional character of into the SiO 2 layer during thermal annealing [25]. Those the QDs confinement potential could be retained even Ga vacancies diffuse into the QDs region during RTA, after RTA at a relatively high temperature (30 s at 900 enhancing the In/Ga interdiffusion through a dot/cap°C [5] or at 950 °C [14] and 60 s [13] at 900 TC). In interface [12,13].…”
Section: Qdsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to a fast Ga outdiffusion has been shown that the three-dimensional character of into the SiO 2 layer during thermal annealing [25]. Those the QDs confinement potential could be retained even Ga vacancies diffuse into the QDs region during RTA, after RTA at a relatively high temperature (30 s at 900 enhancing the In/Ga interdiffusion through a dot/cap°C [5] or at 950 °C [14] and 60 s [13] at 900 TC). In interface [12,13].…”
Section: Qdsmentioning
confidence: 99%
“…The structure investigated was grown by metaloorganrapid thermal annealing (RTA) system with Si0 2 capic vapor phase epitaxy in the Institute of Experimental ping [5,9,[12][13][14] or proximity capping, (which means ic v arpas epity The Gnstiut e oEx erieal an annealing with a piece of GaAs substrate in close Physics, Warsaw University. The GaAs buffer layer was proximity to the sample surface) [3,6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5 We believe that the averaging of the Ge concentration among islands in different layers is one of the main reasons contributing to the narrowing of the PL peaks.…”
Section: Fig 2 ͑A͒mentioning
confidence: 99%
“…1 Photoluminescence ͑PL͒ investigations suggest blueshift in the interband energy and narrowing of the PL linewidth after thermal annealing. [2][3][4] Although the reasons for this shift have been investigated from a microstructural point of view, 5,6 little attention has been paid to the effects of thermal annealing on compositional change within QDs. This letter reports an energy-filtering transmission electron microscopy ͑TEM͒ study of the effects of annealing on QD stacks.…”
mentioning
confidence: 99%